(3OjhGf GdejGMs - (3Gdabjg TLGY GdOjf YeQ GdejGM Gdjefjs
(3ChdgG (B:s
(3hbGd CjVkG jeOM Gdedc GdeLGgO(B: (3CgdG HPG GdWQa GdcMjd ef Ydec JaJfj Hg s
(3BNQgG (B:s
(3CfUafj ef UOc hCNdGac aj hYOc dG MGd dj aj hYOc ef YQac PG GdfGeL s
(3Vef eLehY , JQJjHgG (B: (3ef U (B26 - (3U(B35s
(3GfXQg eY OjhGf GdMcGcs
(3gPG GdOjhGf JSJYed aj GddZI GdMejQjI NUhUkG aj Cd GdJYQjajIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B229 s
Keywords: (3GdCOHs